2022
DOI: 10.1177/23780231221141165
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the 2021 Monthly Child Tax Credit on Child and Family Well-Being: Evidence from New York City

Abstract: The temporary monthly child tax credit implemented in 2021 had the potential to affect many aspects of child and family well-being, including poverty, hardship, use of food pantries, spending on child-related items, and parents’ mental health and employment. The authors assess these effects using data from two longitudinal studies of well-being in New York City. They find that the monthly child tax credit led to significant declines in the risk for facing material hardship, multiple hardships, running out of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Although we expect that, on average, the monthly credit improved the mental health symptoms of parents, some recent studies find null effects of the 2021 CTC on indicators of mental wellbeing ( Collyer et al, 2022 ; Glasner et al, 2022 ). Furthermore, other experimental studies of unconditional cash transfers have found null or negative mental health impacts ( Gennetian et al, 2022 ; Jacob et al, 2022 ; Jaroszewicz et al, 2022 ; Liebman et al, 2022 ; Magnuson et al, 2022 ; Pilkauskas et al, 2023 ).…”
Section: Why Might the 2021 Monthly Ctc Payments Affect The Mental He...mentioning
confidence: 78%
See 4 more Smart Citations
“…Although we expect that, on average, the monthly credit improved the mental health symptoms of parents, some recent studies find null effects of the 2021 CTC on indicators of mental wellbeing ( Collyer et al, 2022 ; Glasner et al, 2022 ). Furthermore, other experimental studies of unconditional cash transfers have found null or negative mental health impacts ( Gennetian et al, 2022 ; Jacob et al, 2022 ; Jaroszewicz et al, 2022 ; Liebman et al, 2022 ; Magnuson et al, 2022 ; Pilkauskas et al, 2023 ).…”
Section: Why Might the 2021 Monthly Ctc Payments Affect The Mental He...mentioning
confidence: 78%
“…Despite growing policy interest in unconditional income supports (e.g., Shaefer et al, 2018 ) and significant correlational evidence of the positive relationship between income and mental health (e.g., Sareen et al, 2011 ), experimental and quasi-experimental evidence on the effects of income on mental health is more mixed. Studies taking a more causal approach to examining the relationship between income and mental health have reported both positive (e.g., Batra et al, 2023 ; Evans & Garthwaite, 2014 ) and null effects of unconditional cash on mental health (e.g., Collyer et al, 2022 ; Gennetian et al, 2022 ; Glasner et al, 2022 ). This study adds to this literature by using a quasi-experimental research method to examine the link between 2021 monthly CTC payments and mental health symptoms among parents with low incomes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations